2022
DOI: 10.3389/fnut.2022.844757
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms of Iron Mediated Programmed Cell Death and Its Roles in Eye Diseases

Abstract: Ferroptosis, a newly identified, iron-dependent type of programmed cell death, is active in several diseases, such as heart disease, brain damage, and cancer. Its main characteristics commonly involve excess iron accumulation, elevated lipid peroxides and reactive oxygen species, and reduced levels of glutathione and glutathione peroxidase 4 levels. The effects of ferroptosis in eye diseases cannot be underestimated, with ferroptosis becoming a research target in ocular disorders and emerging evidence from a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 98 publications
0
11
0
Order By: Relevance
“…DR, characterized by ischemic microvascular disease of the retina and retinal neurodegeneration, is a highly specific complication of diabetes with complex multifactorial pathophysiology, which finally leads to visual impairment or blindness ( 29 ). Emerging evidence from a series of in vivo and in vitro studies revealed that ferroptosis, a new type of iron-dependent programmed cell death linking metabolism, disease, immune cells, and targeted therapy, is closely associated with the pathophysiological states of various ocular diseases, such as corneal alkali burn, glaucoma, age-related macular degeneration, and retinitis pigmentosa ( 6 , 30 32 ). Furthermore, targeting ferroptosis is a promising treatment for ocular diseases ( 6 , 31 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…DR, characterized by ischemic microvascular disease of the retina and retinal neurodegeneration, is a highly specific complication of diabetes with complex multifactorial pathophysiology, which finally leads to visual impairment or blindness ( 29 ). Emerging evidence from a series of in vivo and in vitro studies revealed that ferroptosis, a new type of iron-dependent programmed cell death linking metabolism, disease, immune cells, and targeted therapy, is closely associated with the pathophysiological states of various ocular diseases, such as corneal alkali burn, glaucoma, age-related macular degeneration, and retinitis pigmentosa ( 6 , 30 32 ). Furthermore, targeting ferroptosis is a promising treatment for ocular diseases ( 6 , 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence from a series of in vivo and in vitro studies revealed that ferroptosis, a new type of iron-dependent programmed cell death linking metabolism, disease, immune cells, and targeted therapy, is closely associated with the pathophysiological states of various ocular diseases, such as corneal alkali burn, glaucoma, age-related macular degeneration, and retinitis pigmentosa ( 6 , 30 32 ). Furthermore, targeting ferroptosis is a promising treatment for ocular diseases ( 6 , 31 ). Some studies indicated that the inhibition of ferroptosis can alleviate cell death more effectively than the inhibition of apoptosis and necrosis in age-related macular degeneration ( 9 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The implications of these findings with respect to VK and the EVS are significant. Zhang et al 2022 [205] provide a comprehensive review of ferroptotic biology and its involvement in major ocular diseases, and conclude that the effects of ferroptosis cannot be underestimated, deeming ferroptosis-related cell death to be a critical emerging field of study [205]. Yang et al 2022 [206] provide evidence in human primary RPE cells and in mice that the FSP1-CoQ10/VK-NADH pathways inhibit retinal ferroptotic pathology and may have a potential therapeutic role, providing supporting biochemical, histologic, and electroretinogram data [206].…”
Section: Non-canonical Vitamin K Functions and Ferroptosismentioning
confidence: 99%